Armies without nations : public violence and state formation in Central America, 1821-1960 - Holden, Robert H. (Oxford University Press, 2004)
Public violence, scarcely analyzed and little understood, is the subject of this pathbreaking research into the histories of Guatemala, El Salvador, Honduras, Nicaragua, and Costa Rica. Robert Holden shows how the national and international dimensions of public violence intersected there to produce "armies without nations.